STRUCTURE AND PREVALENCE OF DENTAL DISEASES IN PATIENTS WITH EARLY STAGES OF CHRONIC KIDNEY DISEASE IN AZERBAIJAN - Yusubova, Sh.R.; Huseynova, S.T.; Ahmedzade, U.I.; Niftalieva, S.F. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the features of dental diseases and their distribution in patients with early stages of chronic kidney disease in Azerbaijan. The study involved 179 patients with early stages of chronic kidney disease. Decayed, Missing due to caries, Filled Teeth index, Caries, Fillings and Extractions index, Müllemann bleeding index, Svrakov iodine index, Community Periodontal Index and Gingival Index, Fuchs and Rumford indices were measured. The results showed that in patients with chronic kidney disease generalized periodontitis was present in 81.8 % of cases, and localized periodontitis in 18.2 % of cases, which is 5.4 and 1.7 times more than in the control group, respectively. In the early stages of chronic kidney disease, the prevalence of periodontitis is higher than caries and chronic periodontal diseases. An increase in the DMFT index was observed as kidney function decreased. Fuchs and Svrakov iodine indices were different during chronic kidney disease compared to the control group (р
Keywords: chronic kidney disease; periodontitis; caries; Decayed; Missing due to caries; Filled Teeth index; Svrakov iodine index; gingival index